Financial accounting scandals and the reform of corporate governance in the United States and in Italy. Issue 1 (6th February 2017) - Sorensen, Daniel P.; Miller, Scott E.
Abstract : Purpose: In the 1990s and beginning of the next decade, a series of financial accounting scandals occurred in the United States (USA or US) and in several other countries of the world. The USA and Italy (among others) responded with legislation to reform financial reporting and corporate governance in these jurisdictions. This paper aims to compare the regulatory response of Italy to that of the USA. Design/methodology/approach: This paper includes a review of relevant literature and evaluation of the actions of the regulatory authorities. Findings: In the case of the financial reporting crises, the rapid response put the USA into the role of the "first mover" with the European Union (EU) reacting to US initiatives and eventually converging to a large degree with the provisions of the US legislation. Italy has adopted many of the same regulatory reforms as the USA and has added some reforms that are directed to the specific needs to Italy. Research limitations/implications: In conjunction with legislative initiatives like Sarbanes-Oxley, private enforcement mechanisms, such as shareholder class action suits in the USA, play an important role in discouraging and punishing financial accounting fraud. Practical implications: In the absence of significant reforms of the Italian private enforcement system, corporate governance abuses and the potential for accounting scandals may still be persistent. As a whole, cooperative efforts continue between the USA and the EU. Such efforts are needed more and more, as companies become increasingly globalized. Originality/value: This paper provides comparison and evaluation of corporate governance reform efforts in the USA and Italy.